Key for identification of the parasitoids (Hymenoptera: Braconidae: Aphidiinae) of aphids infesting alfalfa in Europe - Ghaliow, Mustafa E.; Petrović, Andjeljko; Kocić, Korana; Čkrkić, Jelisaveta; Bogdanović, Ana Mitrovski; Starý, Petr; Kavallieratos, Nickolas G.; Tomanović, Željko (Zootaxa, 2018)
Although Aphidiinae parasitoids have been used as agents for biocontrol of alfalfa aphids for more than half a century and have been the subject of numerous ecological investigations, there is an evident lack of systematic studies on the parasitoids of aphids infesting alfalfa in Europe. Here we present an original and up-dated key for identification of both native and invasive Aphidiinae parasitoids attacking aphids that feed on alfalfa in Europe. In total, 20 species are keyed and illustrated with scanning electron micrographs and line drawings.